Self-care Practices of Diabetic Patients toward the Prevention of Osteoporosis in Babylon Governorate, Iraq - Wael Sulaiman Sabea (Journal of Global Pharma Technology, 2019)
Background: Diabetic patients with uncontrolled insulin are exposed to a potential risk of osteoporosis because disorder of osteoblast-osteoclast function and confusion in the metabolism of calcium, phosphorus and vitamin